“I Chose Motherhood First”: Salvaging the Maternal Identity in Resource-Starved Jails - Haakmat, Narissa (The prison journal, 2024)
The population of women in jail increased by 15% from 2008 to 2018. A portion of this increase was due to state policies shifting individuals serving sentences of 1–5 years to local jails to reduce prison overcrowding. In-depth interviews with 62 women serving long-term sentences in local jails in Central and Eastern Kentucky were conducted to examine how they navigated motherhood in this carceral setting. Findings suggested that despite the salient role that motherhood played in their lives, jails provided few meaningful opportunities for women to perform identity-congruent behaviors or receive verification of their maternal identity. Implications for reintegration, desistance, and theoretically relevant intervention models are discussed.